Resistance Mechanisms and Susceptibility to Organophosphates, Carbamates and Pyrethroids in Anopheles Gambiae S.L. Giles (Diptera: Culicidae) In Hohoe District, Ghana. - Kahindi, C.S. (University of Ghana, 2005)
Malaria is a threat to more than 40% of the world's population accounting for more than 300 million acute cases and between 1.1 and 2.7 million deaths annually. Over 90% of the malaria cases are in sub-Saharan Africa, constituting 10% of the total disease burden. Currently activities support the extensive use of insecticide treated materials for malaria control. However these efforts are threatened by the evolution of resistance in the main malaria vectors, Anopheles gambiae s.1. towards the commonly used insecticides for mosquito control. The study was done to determine the susceptibility status and the underlying mechanisms of resistance in An. gambiae s.1 against commonly used insecticides for control in Hohoe District, Volta region of Ghana. Mosquitoes were sampled in four villages; Adabraka, Atabu Newtown, Kledzo and Likpe-Bakwa. Adult mosquitoes were tested against the WHO diagnostic concentrations of 0.75% permethrin, 0.05% deltamethrin, 4% DDT, 5% malathion and 0.1% propoxur. The susceptible Kisumu strain of An. gambiae s.l was used as the reference. Results obtained revealed high levels of resistance to DDT; 6-51% mortality rates in the four villages sampled. Susceptibility to Permethrin was considerably low with 3282% mortality rates. Mortalities were very high with 0.05% Deltamethrin; 91-97%. All field mosquitoes tested were fully susceptible to Malathion with 100% mortality rates across the 4 villages. Susceptibility to Propoxur was similarly higher; 94-95% mortality rates. Median Knockdown times in field populations variously increased compared with the susceptible Kisumu strain; 4-6, 1.5-2 and 3 fold with Permethrin, Deltamethrin and DDT respectively. PCR identification revealed that all the mosquitoes tested were An. gambiae sensu stricto with 64% ‘Savanna’ and 36% ‘Mopti’ forms. The kdr mutation occurred at a frequency of 23.7%, 21.7%, 22.7% and 31% in An. Gambiae populations of Adabraka, Atabu Newtown, Kledzo and Likpe respectively. Over 70% of the kdr mutation occurred in the ‘Savanna’ form. Biochemical mechanisms of resistance were investigated by the CDC microplate assays protocol. There was a significant elevated activity of mixed function oxidases in An. gambiae populations in Likpe as compared to the susceptible Kisumu strain. Activity of Acetylcholine esterase enzyme was significantly elevated in Adabraka population while Glutathione S-transferases showed no significant increase in activity in all the four wild population. There was a significant elevated activity of both α and β-nonspecific esterases in Adabraka and Likpe populations. The high frequency of kdr and elevated activity of several detoxification enzymes indicate the occurrence of multi resistance in An. gambiae populations in Hohoe district. Insecticide resistance has been a problem in all insect groups that are vectors of diseases. Regular testing is therefore vital for mosquito control operations because resistant populations of mosquitoes reduce the effectiveness of control procedures. The main defence against resistance is close surveillance of the susceptibility of vector populations so as to detect changes in their susceptibility status at an early stage and to implement resistance management strategies.